2016
DOI: 10.1101/064204
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of tDCS on motor learning and memory formation: a consensus and critical position paper

Abstract: Motor skills are required for activities of daily living. Transcranial direct current stimulation (tDCS) applied in association with motor skill learning has been investigated as a tool for enhancing training effects in health and disease. Here, we review the published literature investigating whether tDCS can facilitate the acquisition and retention of motor skills and adaptation. A majority of reports focused on the application of tDCS with the anode placed over the primary motor cortex (M1) during motor ski… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
39
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 141 publications
1
39
0
Order By: Relevance
“…The relative small number of subjects and the lack of a control task condition represent further potential limitations. Furthermore, an important discussion surrounding tDCS research is related to how reproducibility of reported effects should be evaluated49. A recent review50 on the effects of tDCS on social cognition pointed out that some studies produced results inconsistent to each other, likely due to methodological differences (e.g., intensity and duration of the stimulation, online vs. offline stimulation, electrode size, scalp placement, study design, experimental task).…”
Section: Discussionmentioning
confidence: 99%
“…The relative small number of subjects and the lack of a control task condition represent further potential limitations. Furthermore, an important discussion surrounding tDCS research is related to how reproducibility of reported effects should be evaluated49. A recent review50 on the effects of tDCS on social cognition pointed out that some studies produced results inconsistent to each other, likely due to methodological differences (e.g., intensity and duration of the stimulation, online vs. offline stimulation, electrode size, scalp placement, study design, experimental task).…”
Section: Discussionmentioning
confidence: 99%
“…It is theorized that pairing tDCS with rehabilitation strategies may lead to more meaningful and lasting benefit (10)(11)(12)(13)(14). A particularly promising application of tDCS is to improve the rate of learning (15)(16)(17) and magnitude of benefit from cognitive training (CT) (14,(18)(19)(20)(21)(22)(23)(24)(25)(26). While many questions remain, pairing tDCS with CT has been shown to increase learning and cognitive performance, particularly in tasks of information processing and working memory (14,18,22,(26)(27)(28)(29).…”
Section: Introductionmentioning
confidence: 99%
“…However, despite encouraging results in human neurophysiological experiments (Nitsche & Paulus, 2000;Stagg & Nitsche, 2011), clinical trials Bikson et al, 2016;Boggio et al, 2008;Brunoni et al, 2013;Fregni et al, 2006;Lefaucheur et al, 2017;Valle et al, 2009) and detailed characterization of its physiological mechanisms of action in animal models (Bikson et al, 2004;Ironside et al, 2018;Jackson et al, 2016;O'Shea & Revol, 2017), questions remain about protocol optimization, especially as relating to inter-and intra-individual variability (Chew, Ho, & Loo, 2015;Dyke, Kim, Jackson, & Jackson, 2016;Horvath, Vogrin, Carter, Cook, & Forte, 2016;Lopez-Alonso, Fernandez-Del-Olmo, Costantini, Gonzalez-Henriquez, & Cheeran, 2015;Worsching et al, 2017). The integration of tDCS with modern neuroimaging techniques (Saiote, Turi, Paulus, & Antal, 2013;Turi, Paulus, & Antal, 2012) is likely to represent a key methodological approach for advancing our understanding of the functional correlates of tDCS mechanisms in terms of changes in patterns of brain activation and for understanding individual differences in response to stimulation (Buch et al, 2017;Esmaeilpour et al, 2018;Giordano et al, 2017).…”
mentioning
confidence: 99%